Treatment of risdiplam after nusinersen continuously improves upper limb motor function in spinal muscular atrophy patients: a multicenter experience - Cheng, Xi; Ma, Yun; Yu, Li-Qiang; Fan, Ya-Bei; Zhu, Liang-Hua; Lu, Han-Bing; Niu, Qi (Frontiers in Pediatrics, 2026)
IntroductionSome individuals with spinal muscular atrophy (SMA) transition from nusinersen to risdiplam during disease-modifying therapy (DMT) due to factors such as treatment convenience, economic considerations, and adverse events (AEs). This study evaluates the safety and effectiveness of switching DMTs by analyzing real-world clinical data from multiple centers in China.MethodsPatients with 5q-SMA who switched from nusinersen to risdiplam were enrolled from four medical institutions in Jiangsu Province. The reasons for switch, as well as any adverse events experienced, were documented. Assessments of motor function were conducted prior to treatment, following the switch, and at four-month intervals subsequently.ResultsA total of eleven patients were included in this retrospective analysis. RULM scores showed maintains improvement following the switch compared to baseline measurements prior to treatment initiation. No significant adverse events were reported after the switch.ConclusionDespite the small sample size and lack of a control group, these findings suggest that switching from nusinersen to risdiplam in real-world clinical settings is safe and allows for continued improvement of motor function in SMA patients.